The effect of different priming treatments on germination traits of Securigera securidaca seeds under low temperature stress - F. Sharifzadeh; Arezoo Espanany; Mohammad Reza Naghavi (علوم و فناوری بذر ایران)
In this research, the effect of different seed priming treatments was investigated on seed germination parameters of Securigera securidaca seeds in the low temperature stress conditions. Seeds first were exposed to eight temperature levels (5, 10, 15, 20, 25, 30, 35 and 40 ° C). Experimental treatments included different priming treatments (hydropriming, osmopriming including potassium nitrate and calcium chloride and no priming). The results showed that temperature significantly reduced germination percentage and rate, seedling length and seedling dry weight, normal seedling percentage and seed vigor. 5 mM of calcium chloride treatment at 10 ° C for 20 hours had the highest germination percentage, and 1% of potassium nitrate treatment at 10 ° C for 20 hours had the maximum seedling dry weight and 0.5% of potassium nitrate at 10 ° C for 20 hours and 10 mM of calcium chloride treatments at 15 ° C for 20 hours had the highest percentage of normal seedlings. Hydropriming treatment at 15 ° C for 20 hours had the highest germination rate, seedling length and seed vigor and was also one of the best treatments in terms of normal seedling percentage. So this treatment can be introduced as a suitable treatment for this plant because it is better in most germination traits and it is easier and cheaper to do.